Loss of the GPI‐anchor in B‐lymphoblastic leukemia by epigenetic downregulation of PIGH expression. Issue 1 (25th November 2018) - Loeff, Floris C.; Rijs, Kevin; van Egmond, Esther H. M.; Zoutman, Willem H.; Qiao, Xiaohang; Kroes, Wilhelmina G. M.; Veld, Sabrina A. J.; Griffioen, Marieke; Vermeer, Maarten H.; Neefjes, Jacques; Frederik Falkenburg, J. H.; Halkes, Constantijn J. M.; et al.
Abstract: Adult B‐lymphoblastic leukemia (B‐ALL) is a hematological malignancy characterized by genetic heterogeneity. Despite successful remission induction with classical chemotherapeutics and novel targeted agents, enduring remission is often hampered by disease relapse due to outgrowth of a pre‐existing subclone resistant against the treatment. In this study, we show that small glycophosphatidylinositol (GPI)‐anchor deficient CD52‐negative B‐cell populations are frequently present already at diagnosis in B‐ALL patients, but not in patients suffering from other B‐cell malignancies. We demonstrate that the GPI‐anchor negative phenotype results from loss of mRNA expression of the PIGH gene, which is involved in the first step of GPI‐anchor synthesis. Loss of PIGH mRNA expression within these B‐ALL cells follows epigenetic silencing rather than gene mutation or deletion. The coinciding loss of CD52 membrane expression may contribute to the development of resistance to alemtuzumab (ALM) treatment in B‐ALL patients resulting in the outgrowth of CD52‐negative escape variants. Additional treatment with 5‐aza‐2′‐deoxycytidine may restore expression of CD52 and revert ALM resistance.